Brain–computer interfaces and personhood: interdisciplinary deliberations on neural technology. (11th November 2019) - Sample, Matthew; Aunos, Marjorie; Blain-Moraes, Stefanie; Bublitz, Christoph; Chandler, Jennifer A; Falk, Tiago H; Friedrich, Orsolya; Groetzinger, Deanna; Jox, Ralf J; Koegel, Johannes; McFarland, Dennis; Neufield, Valerie; et al.
Abstract: Objective . Scientists, engineers, and healthcare professionals are currently developing a variety of new devices under the category of brain–computer interfaces (BCIs). Current and future applications are both medical/assistive (e.g. for communication) and non-medical (e.g. for gaming). This array of possibilities has been met with both enthusiasm and ethical concern in various media, with no clear resolution of these conflicting sentiments. Approach . To better understand how BCIs may either harm or help the user, and to investigate whether ethical guidance is required, a meeting entitled 'BCIs and Personhood: A Deliberative Workshop' was held in May 2018. Main results . We argue that the hopes and fears associated with BCIs can be productively understood in terms of personhood, specifically the impact of BCIs on what it means to be a person and to be recognized as such by others. Significance . Our findings suggest that the development of neural technologies raises important questions about the concept of personhood and its role in society. Accordingly, we propose recommendations for BCI development and governance.